Analisa Rugi Daya, Drop Tegangan dan Perbaikan pada Sistem Distribusi Penyulang Keboansikep PT PLN (Persero) UP3 Sidoarjo - Pradana, Fendy Steyo; Jamaaluddin, Jamaaluddin; Anshory, Izza; Ayuni, Shazana Dhiya (Universitas Syiah Kuala, 2025)
Abstract:This research analyzes the technical and economic performance improvements of the 20 kV Keboansikep feeder network using ETAP 21.0.1 simulation software. The study addresses the problem of high power losses and voltage drops in the existing system, which reduce network efficiency and electricity supply quality. Data collection involved field measurements of feeder load, conductor specifications, transformer capacity, and network configuration, followed by modeling and simulation in ETAP. Two improvement scenarios were evaluated: Option 1, upgrading conductor cross-sectional area to 240 mm, and Option 2, adding a new feeder line to distribute the load more evenly. Simulation results show that in the existing condition, total power loss reached 246.11 kW with a maximum voltage drop of 3.8%. Option 1 reduced power loss to 153.08 kW and voltage drop to 2.5%, while Option 2 achieved the best performance with power loss of only 65.99 kW and voltage drop of 1.2%. From an economic perspective, Option 1 generated annual energy cost savings of approximately IDR 896 million, while Option 2 saved around IDR 1.73 billion annually. Although Option 2 requires higher investment, it offers greater long-term benefits in terms of energy efficiency, voltage stability, and operational reliability. The findings provide practical insights for electricity distribution companies in selecting cost-effective and technically sound solutions to minimize network losses and enhance service quality.